A clinical informatics approach to bronchopulmonary dysplasia: current barriers and future possibilities - Moreira, Alvaro G.; Husain, Ameena; Knake, Lindsey A.; Aziz, Khyzer; Simek, Kelsey; Valadie, Charles T.; Pandillapalli, Nisha Reddy; Trivino, Vanessa; Barry, James S (Frontiers in Pediatrics, 2024)
Bronchopulmonary dysplasia (BPD) is a complex, multifactorial lung disease affecting preterm neonates that can result in long-term pulmonary and non-pulmonary complications. Current therapies mainly focus on symptom management after development of BPD indicating a need for innovative approaches to predict and identify neonates who would benefit most from targeted or earlier interventions. Clinical informatics, a subfield of biomedical informatics, is transforming healthcare by integrating computational methods with patient data to improve patient outcomes. The application of clinical informatics to develop and enhance clinical therapies for BPD presents opportunities by leveraging electronic health record data, applying machine learning algorithms, and implementing clinical decision support systems. This review highlights the current barriers and the future potential of clinical informatics in identifying clinically relevant BPD phenotypes, and developing clinical decision support tools to improve the management of extremely preterm neonates developing or with established BPD. However, the full potential of clinical informatics in advancing our understanding of BPD with the goal of improving patient outcomes can’t be achieved unless we address current challenges such as data collection, storage, privacy, and inherent data bias.